2012
DOI: 10.1615/intjmedmushr.v14.i5.110
|View full text |Cite
|
Sign up to set email alerts
|

Yield Performance of Lingzhi or Reishi Medicinal Mushroom, Ganoderma lucidum (W.Curt.:Fr.) P. Karst. (Higher Basidiomycetes), Using Different Waste Materials as Substrates

Abstract: In this research the effect of sawdust, malt extract, and wheat bran on yield, biological efficiency (BE), and mycelia growth of Ganoderma lucidum was investigated. Three kinds of sawdust (beech, poplar, and hornbeam) as basal medium were mixed with two levels of wheat bran (5% and 10% w/w) and malt extract (2.5% and 5% w/w) as medium supplement for production of G. lucidum in factorial experiments on the basis of completely randomized design with three replications. The results showed that various kinds of sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 7 publications
2
16
0
Order By: Relevance
“…Cultivable strains can biodegrade a wide range of lignocellulosic substrates, implying outstanding catabolic performance. 15,16 In the case of the strain evaluated in this study (G. lucidum E47), its biodegradative potential seems to be comparable to that of highly ligninolytic strains of Pleurotus ostreatus. 17 Fiber analysis has shown that the physiology of its catabolic activity acts differentially on hemicellulose or cellulose fractions, exerting low or high ligninolytic activity according to the lignocellulosic nature of the substrate.…”
mentioning
confidence: 75%
“…Cultivable strains can biodegrade a wide range of lignocellulosic substrates, implying outstanding catabolic performance. 15,16 In the case of the strain evaluated in this study (G. lucidum E47), its biodegradative potential seems to be comparable to that of highly ligninolytic strains of Pleurotus ostreatus. 17 Fiber analysis has shown that the physiology of its catabolic activity acts differentially on hemicellulose or cellulose fractions, exerting low or high ligninolytic activity according to the lignocellulosic nature of the substrate.…”
mentioning
confidence: 75%
“…Its fruiting body is named as "Reishi" in Japanese and "Lingzhi" in Chinese [1,2]. World-wide Reishi occupies a major source of medicine that has been used for more than 2000 years [3][4][5]. Commercial G. lucidum products are available in various forms, such as powders, dietary supplements, and tea which are farmed from different parts of the mushroom, including mycelia, spores, and fruit body [4].…”
Section: Introductionmentioning
confidence: 99%
“…Commercial G. lucidum products are available in various forms, such as powders, dietary supplements, and tea which are farmed from different parts of the mushroom, including mycelia, spores, and fruit body [4]. G. lucidum has been used in Traditional Chinese Medicine (TCM) as a remedy to treat more than 20 different illnesses which include migraine and headache, hypertension, arthritis, bronchitis, asthma, anorexia, gastritis hemorrhoids, hyper-cholesterolaemia, nephritis, dysmenorrhoea, constipation, lupus erythematosis, hepatitis, leucopoenia, cardiovascular problems and cancer [3,[6][7][8]. Besides, reishi or lingzhi also attribute some health benefits which principally include the control of blood glucose levels, modulation of the immune system, hepato-protection, and bacteriostasis [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, Ganoderma grew on corn cobs with a BE of 5.32% while saw dust had a minimal BE of 0.05%. In previous studies, Erkel (2009) grew Ganoderma on Poplar, Beech and Oak sawdusts and obtained an average BE of 15.09% while Azizi et al (2012) achieved a BE of 12.89% on Hornbeam sawdust and a high 18.68% on Poplar sawdust. Veena and Pandey (2010) reported a BE ranging from 4 to 13% when they cultivated G. lucidum on locally available saw dust in India.…”
Section: Discussionmentioning
confidence: 92%